2001
DOI: 10.1016/s0377-2217(00)00177-6
|View full text |Cite
|
Sign up to set email alerts
|

Routing order pickers in a warehouse with a middle aisle

Abstract: This paper considers a parallel aisle warehouse, where order pickers can change aisles at the ends of every aisle and also at a cross aisle halfway along the aisles. An algorithm is presented that can find shortest order picking tours in this type of warehouses. The algorithm is applicable in warehouse situations with up to three aisle changing possibilities.Average tour length is compared for warehouses with and without a middle aisle. It appears that in many cases the average order picking time can be decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
15

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(130 citation statements)
references
References 6 publications
1
96
0
15
Order By: Relevance
“…Ratliff and Rosenthal (1983) use dynamic programming to find an optimal route for a rectangular, narrow aisles and single-block warehouse. De Koster et al (1998) and Roodbergen and De Koster (2001) extend the method for a warehouse where the I/O point location is decentralized and warehouses with a middle aisle (2 blocks). Instead of the optimal routing methods, heuristics are commonly used in practice because they are easy to implement and maintain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ratliff and Rosenthal (1983) use dynamic programming to find an optimal route for a rectangular, narrow aisles and single-block warehouse. De Koster et al (1998) and Roodbergen and De Koster (2001) extend the method for a warehouse where the I/O point location is decentralized and warehouses with a middle aisle (2 blocks). Instead of the optimal routing methods, heuristics are commonly used in practice because they are easy to implement and maintain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a penalty to pay for inserting a middle cross aisle: it reduces floor space that could otherwise be allocated to storage, and therefore requires a slightly larger facility to maintain the same amount of storage. However, when more than one location is visited in a single tour, the addition of a cross aisle creates more possible routes for travel between locations and therefore has the potential to reduce expected travel [15]. For single-command travel, Layouts A and C are preferred, whereas Layouts B and C are generally preferred for dual-command travel [13].…”
Section: Introductionmentioning
confidence: 99%
“…They found that Sshape heuristics perform well in the narrow-aisle high-bay pallet with many items scenario. Roodbergen and Koster [14] used dynamic programming to formulate the shortest traveling path for a warehouse with three cross aisles. Other research related to design and planning of warehousing systems can be found in Cormier and Gunn [15], Cormier [16], Van den Berg and Zijm [17] and Rouwenhorst et al [18].…”
Section: Literature Reviewmentioning
confidence: 99%